Ultrastructure of the Lyonet's glands in larvae of Diatraea saccharalis Fabricius (Lepidoptera: Pyralidae) - Victoriano, Eliane [UNESP]; Gregório, Elisa A. [UNESP] (My University, 2004)
The Lyonet's gland is found in Lepidoptera larvae, close to the excretory duct of the silk gland. The role played by this gland is still uncertain. This work aims to describe the ultrastructure of the Lyonet's gland in Diatraea saccharalis larvae, offering suggestions regarding its possible function. The insects were reared under laboratory-controlled conditions. The glands were conventionally prepared for transmission (TEM) and scanning (SEM) electron microscopy. SEM showed that Lyonet's glands are paired small structures located in the ventral side of the head. They are composed by clustered long cells resembling leaves. Under TEM observations, each cell is surrounded by a thin basal lamina and contains large stellate nucleus. The cytoplasm presents large and empty canaliculi with small microvilli. The basal plasma membrane forms numerous infoldings where numerous and well-developed mitochondria are concentrated. The cytoplasmic membrane system is poorly developed. Our ultrastructural results suggest that the Lyonet's gland in D. saccharalis larvae may be involved in the uptake of small molecules from the hemolymph; no morphological evidences of macromolecules synthesis and secretion were noticed. The detection of nerve fibers in the gland suggest a neural control for the glandular cell function.
Keywords: Accessory gland; Insect; Morphology; Sugarcane borer